Evaluation of the readability of informed consent forms commonly used in dermatology and cosmetology in Turkiye - Mine Mujde Kus (Medicine Science)
Informed consent forms (ICFs) must contain all the necessary information related to medical interventions and be comprehensible to the patient. This study aims to determine the readability levels of the ICFs listed on the official website of the Turkish Dermatology Association. A total of 23 consent forms, accessible on the website (https://turkdermatoloji.org.tr/icerik/detay/289) of the Turkish Dermatology Association, were incorporated into the study and classified into seven distinct categories. Twenty-three consent forms available on the Turkish Dermatology Association's website were included in the study and categorized into seven groups. The texts of these forms were loaded into readability software. To ascertain the readability levels of the included texts, the mean number of words per sentence, the mean word count, the mean number of words with four syllables or more, and the mean number of syllables were calculated using the Bezirci-Yılmaz and Ateşman formulas. These data were then statistically compared. The mean readability of all ICFs was at the high school level according to the Bezirci-Yılmaz formula and at a medium difficulty level according to the Ateşman formula. According to the Bezirci-Yılmaz formula, the Methotrexate ICF was at an academic level, while the ICFs for Cosmetic Procedures with Energy-Based Devices and Superficial Skin Renewal Methods were at the undergraduate level. When comparing the readability values of Bezirci-Yılmaz and Ateşman, a significant difference was found between five groups with multiple consent forms (p=0.006 for both). Pairwise comparisons revealed that the low readability of the ICFs for Cosmetic Procedures with Energy-Based Devices was responsible for this significant difference. The readability of these forms was at the undergraduate level, according to Bezirci-Yılmaz, and at a challenging level, according to Ateşman. The readability levels of the ICFs available on the official website of the Turkish Dermatology Association are low. These consent forms should be revised to guarantee that patients are sufficiently informed about the medical procedures they will undergo. Otherwise, patients and physicians may face legal challenges due to potential complications. [Med-Science 2024; 13(4.000): 949-56]